Maqasid and the Challenges of Modernity - Wael B. Hallaq (Al-Jami'ah Research Centre, 2011)
A central feature of public Muslim discourse over the past three decades has been the call to restore the Shari‘a in one form or another. Some reformers have proposed a new theoretical underpinning for this restoration, arguing for the adoption of foundational concepts that bear little, if any, resemblance to their pre-modern counterparts. A central question that ineluctably emerges in this aporia is: What narrative must be adopted as the representation of the historical Shari‘a, the Shari‘a that prevailed until the early portion of the nineteenth century? If the colonial narrative is ipso facto programmatic and teleological, and if it served and still serves the purposes of all but those of the subaltern majority, then what other narrative must be adopted in the project of creating the new symbiosis? And if the jural voices of the subaltern are to come in for serious consideration, then how are we to represent them, if we can at all? And if we cannot, then into what espistemic predicament, if not a perennial aporia, does this throw both the privileged scholar and the reformer/intellectual? This article does not provide answers to these questions but rather addresses the problematics that these and related questions raise in dealing with the challenge of introducing into the modern Muslim condition one form of Islamic law or another.